About Making Lignin Great Again—Some Lessons From the Past - Glasser, Wolfgang G. (Frontiers in Chemistry, 2019)
Lignin is the second most abundant polymer on Earth, and it can become one of the most important components of sustainable materials manufactured. This requires understanding its structure and the chemical options for compatibilizing it with other polymeric partners in engineered materials.